Contrasting noises and expanding sounds: the composition process of Caminantes I to IV - Maia, Igor Leão (Revista Vórtex, 2018)
This article explores some of the compositional techniques of a cycle of four pieces called Caminantes. Firstly, it comments on the importance of timbre and texture, the starting point for my own creation of material and its articulation. In this part, the contributions of different composers of the 20th Century are discussed, in order to contextualise the ideas and techniques used in the composition of the Caminantes cycle. Then there is an analysis of the compositions from the point of view of form, extended techniques, harmony, microtonality and indeterminacy. The analysis is aided by digital audio analysis, i.e. spectrograms as well as by sections of the score.